1998
DOI: 10.1111/j.1528-1157.1998.tb01291.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Short‐Term Antiepileptic Drug Treatment in Children Result in Cognitive or Behavioral Changes?

Abstract: Summary:Purpose: To determine possible cognitive and behavioral effects of antiepileptic drug (AED) therapy by assessing children with newly diagnosed epilepsy before and after initiation of treatment. A comparison group of children with diabetes mellitus (DM) was included to control for the effects of practice, maturation, and chronic illness.Methods: Baseline neuropsychological assessments were completed for children with epilepsy (n = 37) and children with DM (n = 26) recruited through outpatient clinics at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 22 publications
0
33
1
2
Order By: Relevance
“…In this study, neuropsychological assessment was not conducted as close to "onset" as it had been in other studies 9,10 ; however, age at onset in those studies was defined as a diagnosis of epilepsy following the second unprovoked seizure, so our studies might not be very different in this regard. Effect sizes were generally small, which suggests that the degree of neuropsychological impairment is subtle; however, these indices are attenuated to some degree by the restriction of range in cognitive dysfunction due to exclusion of children with early onset and IQ Ͻ70.…”
Section: Figure 2 Neuropsychological Factor Scores By Antiepileptic Dmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, neuropsychological assessment was not conducted as close to "onset" as it had been in other studies 9,10 ; however, age at onset in those studies was defined as a diagnosis of epilepsy following the second unprovoked seizure, so our studies might not be very different in this regard. Effect sizes were generally small, which suggests that the degree of neuropsychological impairment is subtle; however, these indices are attenuated to some degree by the restriction of range in cognitive dysfunction due to exclusion of children with early onset and IQ Ͻ70.…”
Section: Figure 2 Neuropsychological Factor Scores By Antiepileptic Dmentioning
confidence: 99%
“…5 Supporting studies have been limited by small sample sizes (n ϭ 12-72 for most), [6][7][8][9][10][11][12][13] exclusion of seizure types/ etiologies, [6][7][8][9][10] long latencies between seizure onset and cognitive assessment, 7,8,12,14 using gross outcome measures 11,12,14 or testing limited functions, 6 no control group, 12,14 using retrospective report, 14 or ignoring prior unrecognized seizures, observed in one third of children. 15,16 Understanding risk factors for early neuropsychological deficiencies is critical for early intervention for common cognitive and academic comorbidities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…55 In one Class II study, 15 of 163 children assigned to AED withdrew because of intolerable side effects, 56 and in another, children taking PB did not show an expected increase in IQ on retest. 57 In three other studies, which included 48 children taking VPA, 1 taking PHT, and 51 taking CBZ, evidence was not seen of behavioral or cognitive impairment [58][59][60] (see table 5). A report from the American Academy of Pediatrics 44 regarding general recommendations for awareness of behavioral and cognitive effects of AED noted that high blood levels of some AED (PHT, PB, primidone) were significantly related to cognitive decline.…”
Section: What Are the Nature And Frequency Of Side Effects Of Aed Commentioning
confidence: 99%
“…Although some early studies reported higher academic achievement for females than for males with epilepsy (16-18), others found no main effect for gender (7,19). In a recent study, Austin and colleagues (10) found males with high severity epilepsy to have the most risk for underachievement.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 98%